Induction of CYP3A activity by dexamethasone may not be strong, even at high doses: insights from a case of tacrolimus co-administration - Yoshiyuki Ohno; Toyohito Oriyama; Akira Honda; Mineo Kurokawa; Tappei Takada (BMC, 2023)
Abstract Background Dexamethasone (DEX) induces CYP3A activity in a concentration-dependent manner. However, no study has examined changes in the blood concentration of CYP3A substrate drugs when DEX is administered at high doses. Herein, we present a case in which tacrolimus (TAC), a typical CYP3A substrate drug, was co-administered with a chemotherapy regimen that included high-dose DEX. Case presentation A 71-year-old woman underwent liver transplantation for hepatocellular carcinoma 18 years prior to her inclusion in this case study. She was receiving TAC orally at 2 mg/day and had a stable trough blood concentration of approximately 4 ng/mL and a trough blood concentration/dose (C/D) ratio of approximately 2. The patient was diagnosed with post-transplant lymphoproliferative disease (histological type: Burkitt's lymphoma) after admission. Thereafter, the patient received cyclophosphamide-prednisolone (CP), followed by two courses of R-HyperCVAD (rituximab, cyclophosphamide, doxorubicin, vincristine, and DEX) and R-MA (rituximab, methotrexate, and cytarabine) replacement therapy. DEX (33 mg/day) was administered intravenously on days 1-4 and days 11-14 of R-HyperCVAD treatment, and aprepitant (APR) was administered on days 1-5 in both courses. The TAC C/D ratio decreased to approximately 1 on day 11 during both courses, and then increased. Furthermore, a decreasing trend in the TAC C/D ratio was observed after R-MA therapy. The decrease in the TAC C/D ratio was attributed to APR administration rather than to DEX. Conclusion The induction of CYP3A activity by a high dose of DEX may not be strong. The pharmacokinetic information on DEX and in vitro enzyme activity induction studies also suggested that CYP3A activity induction is not prominent under high-dose DEX treatment.